2013
DOI: 10.1371/journal.pone.0074266
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Plant Compound Geraniin as a Novel Hsp90 Inhibitor

Abstract: Besides its function in normal cellular growth, the molecular chaperone heat shock protein 90 (Hsp90) binds to a large number of client proteins required for promoting cancer cell growth and/or survival. In an effort to discover new small molecules able to inhibit the Hsp90 ATPase and chaperoning activities, we screened, by a surface plasmon resonance assay, a small library including different plant polyphenols. The ellagitannin geraniin, was identified as the most promising molecule, showing a binding affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…The current findings showed that geraniin resulted in a significant timedependent suppression of phosphorylated Akt proteins with a concomitant decreased ratio of p-Akt/Akt. This phenomenon was in accordance with the previous study showing that geraniin exhibited significant dose-depen-dent reduction of p-Akt in both Jurkat and HepG2 cells [48] . Activated Akt leads to the survival of tumor and attenuates apoptosis via phosphorylation of multiple downstream targets including mTOR and GSK-3β.…”
Section: Discussionsupporting
confidence: 93%
“…The current findings showed that geraniin resulted in a significant timedependent suppression of phosphorylated Akt proteins with a concomitant decreased ratio of p-Akt/Akt. This phenomenon was in accordance with the previous study showing that geraniin exhibited significant dose-depen-dent reduction of p-Akt in both Jurkat and HepG2 cells [48] . Activated Akt leads to the survival of tumor and attenuates apoptosis via phosphorylation of multiple downstream targets including mTOR and GSK-3β.…”
Section: Discussionsupporting
confidence: 93%
“…Under the same experimental conditions, IC 50 values for 17-AAG treatment were 2.1 AE 0.3 mM in A375 and 9.6 AE 0.15 mM in Jurkat cell lines, in agreement with those reported by Dal Piaz et al 19 and Liu et al 20 Interestingly, the cytotoxic effect found for compound 1 was in line with SPR analyses, which disclosed 1 as one of the most efficient binders to the immobilized recombinant Hsp90a (K D of 76 AE 7 nM). Compound 17 exhibited IC 50 values of 150 AE 0.3 mM in both cancer cell lines, while 2, 6-8 and 12 had no cytotoxicity.…”
supporting
confidence: 91%
“…19,23 The proteolytic patterns obtained, performed both on Hsp90a and on the Hsp90a/1 complex, using trypsin or chymotrypsin as proteolytic agents, are summarized in Fig. 19,23 The proteolytic patterns obtained, performed both on Hsp90a and on the Hsp90a/1 complex, using trypsin or chymotrypsin as proteolytic agents, are summarized in Fig.…”
mentioning
confidence: 99%
“…Geraniin is a polyphenolic compound that has a wide range of bioactive properties, including anti-oxidant activity, protecting from infections, exerting immunological effects, and inducing metabolic changes [13]. Several studies have demonstrated that geraniin suppresses lung cancer by inhibiting the TGF-β1-induced epithelial-mesenchymal transition [14], exerts a protective effect against osteoporosis in ovariectomized rats [15], and inhibits the chaperone activity of Hsp90 thus providing a multi-targeted approach against cellular oncogenic processes [16]. In our previous studies, geraniin showed efficient radical scavenging activities, including scavenging of superoxide and DPPH radicals, as well as an excellent reducing power [17].…”
Section: Introductionmentioning
confidence: 99%